2021
DOI: 10.3390/microorganisms9051084
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Infection of the Biomphalaria glabrata Vector Snail by Schistosoma mansoni Parasites Drives Snail Microbiota Dysbiosis

Abstract: Host-parasite interaction can result in a strong alteration of the host-associated microbiota. This dysbiosis can affect the fitness of the host; can modify pathogen interaction and the outcome of diseases. Biomphalaria glabrata is the snail intermediate host of the trematode Schistosoma mansoni, the agent of human schistosomiasis, causing hundreds of thousands of deaths every year. Here, we present the first study of the snail bacterial microbiota in response to Schistosoma infection. We examined the interpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 73 publications
(110 reference statements)
5
31
0
Order By: Relevance
“…The top 10 microbial genera (79.21%) were Chryseobacterium (21.64%), Cloacibacterium (12.57%), Flavobacterium (10.54%), Azonexus (9.62%), Aeromonas (7.81%), Acidovorax (6.98%), TH137 (4.13%), Pedobacter (2.89%), Rhodoferax (1.71%), and Vogesella (1.32%). Most of these genera have also been detected in other snails in previous studies based on 16S rRNA sequencing ( 7 , 17 20 ), and among them, Chryseobacterium , Cloacibacterium , and Flavobacterium are affiliated with the aerobic order Flavobacteriales , which are well-known for lipid and carbohydrates metabolism ( 21 , 22 ), while members of Burkholderiales , including Azonexus , Acidovorax , Rhodoferax , and Vogesella , are hydrocarbon-utilizing and denitrifying bacteria ( 23 , 24 ). These results suggested that B. glabrata microbiome may play an important role in host metabolism and physiological adaptations, prompting further exploration of carbon and nitrogen metabolic pathways.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…The top 10 microbial genera (79.21%) were Chryseobacterium (21.64%), Cloacibacterium (12.57%), Flavobacterium (10.54%), Azonexus (9.62%), Aeromonas (7.81%), Acidovorax (6.98%), TH137 (4.13%), Pedobacter (2.89%), Rhodoferax (1.71%), and Vogesella (1.32%). Most of these genera have also been detected in other snails in previous studies based on 16S rRNA sequencing ( 7 , 17 20 ), and among them, Chryseobacterium , Cloacibacterium , and Flavobacterium are affiliated with the aerobic order Flavobacteriales , which are well-known for lipid and carbohydrates metabolism ( 21 , 22 ), while members of Burkholderiales , including Azonexus , Acidovorax , Rhodoferax , and Vogesella , are hydrocarbon-utilizing and denitrifying bacteria ( 23 , 24 ). These results suggested that B. glabrata microbiome may play an important role in host metabolism and physiological adaptations, prompting further exploration of carbon and nitrogen metabolic pathways.…”
Section: Resultsmentioning
confidence: 77%
“…Therefore, research on snails, especially their adaptability and livability, from the perspective of gut microbiota has received increasing attention. Scientists now have a preliminary understanding of snail gut microbiota composition by using high-throughput culture method or 16S rRNA gene sequencing ( 4 7 ). However, culturomics techniques cannot identify the so-called “not yet culturable” microorganisms and 16S rRNA sequencing is limited by the heterogeneity of amplification and low resolution of species annotation ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Antibiotics often disturb microbiomes by decreasing useful and/or increasing harmful bacteria (Akbar et al, 2020). Of the four most common bacterial genera found in the flora of 200 snails, Acinetobacter and Vibrio are both responsive to tetracycline, suggesting a biological linkage between antibiotic presence and infection susceptibility is possible in this system (Portet et al, 2021). The alterations observed in parasite development time, parasite production, and host production from addition of tetracycline are congruent with research findings of microbiome-related impaired immune function following parasitic infection (Portet et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, immune priming is naturally induced by the gut microbiome during Plasmodium infections in Anopheles gambiae , and removal of this priming effect resulted in a higher incidence of infection severity and re-infections (Rodrigues et al, 2010). In other systems, an inverse relationship between host, gut microbiota composition and susceptibility to parasite infection has been described, with differences observed in the microbiomes of S. mansoni -resistant and susceptible Biomphalaria snails (Cortés et al, 2020, Portet et al, 2021). However, the influence of antibiotics in host-parasite systems is not limited to host microbiomes.…”
Section: Introductionmentioning
confidence: 99%
“…The associated microbiota of aquatic organisms often play a crucial role in the host's resistance or tolerance to pathogen infection (Kimura & Tomaru 2014, Dheilly et al 2015, Greenspan et al 2019, Davoodi & Foley 2020, Schellenberg et al 2020, Portet et al 2021. For instance, Huot et al (2020) reported a congruence of vector snails' phylogeny and their associated microbiome, combined with variable susceptibility between snail species and even populations of the same species, suggesting that the snail's microbiome might play a role in parasite resistance.…”
Section: Role Of the Microbiome In The Host Defence Against Natural Enemiesmentioning
confidence: 99%